Ethnobotanical And Ethnopharmacological Study Of Plants Used By The Dumagat Tribe In Angat Dam Watershed, Norzagaray, Bulacan, Philippines - Lopez, John Angelo G; Camacho, Larien D; Dela Cruz; Rachelle T.; Perez, Kareen M; Tumale, Ara Nicole G; Jazul, Regina A. (Science and Community Pharmacy Journal, 2023)
This research on Ethnobotanical and Ethnopharmacological study is a documentation of plants used by the Dumagat Tribe in Angat Dam Watershed, Norzagaray, Bulacan, Philippines. The researchers used snowball sampling technique as a method to identify potential subjects of the study. A total of 100 respondents were interviewed using validated semi-structured questionnaire including the demographic profile of respondents, together with the Ethnobotanical and Ethnopharmacological data of plants. It was noted that most of the respondents are aged between 51-59 years old, majority were male, married, catholic, with rattan making as their source of livelihood. 124 plants were collected and presented to the respondents and noted that leaves was the most frequently used part. The use value (UV), fidelity level (FL), and informant consensus factor (ICF) were calculated for each plant species used to treat various ailments. The plant with the highest use value was Blumea balsamifera (0.69) and the maximum fidelity level of 100% was found for 23 plant species. In the case of ICF, the highest value of 0.9501 was cited for diseases of the respiratory system. The wide variety of plants documented in Angat Dam Watershed can open path for furnishing novel information leading to future studies that would provide recognition of this undocumented knowledge to improve healthcare.